Analysis of filling the maternal and child health handbook for antenatal care - Aenurida Aenurida; Siti Syamsiah; Rukmaini Rukmaini (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Midwife compliance in completely and consistently filling out the Maternal and Child Health (MCH) Handbook is an essential pillar for providing quality Antenatal Care (ANC). The MCH Handbook functions as an instrument for early risk detection, a portable medical record, and a communication tool among healthcare professionals. In practice, however, the level of midwife compliance still faces various challenges that risk diminishing the quality of maternal and child health services.. Purpose: To analysis of the factors influencing midwife compliance in filling out the MCH Handbook using the theoretical framework of the Theory of Planned Behavior (TPB). Method: A descriptive qualitative approach, specifically focusing on exploratory study. The study took place May - September 2025, in North Cikarang, Bekasi. Using total sampling 16 participants were selected, contributor informant inquired midwives providing ANC services, midwife coordinators, heads of puskesmas, and district health office officials. Data collection was carried out using in-depth interviews. The data were analysed using thematic analysis technique. Results: Midwives’ completion of the Maternal and Child Health (MCH) Handbook is influenced by both intrinsic factors, such as professional duty and commitment to quality care, and external factors, including regulatory requirements and institutional demands like BPJS claims. Despite challenges such as limited training, complex handbook sections, high patient loads, and duplicated documentation, effective teamwork, well-established Standard Operating Procedures (SOPs), and strict supervision can enhance accurate and consistent record-keeping. The handbook is valued as a critical tool for continuity of care, early risk detection, provider communication, maternal education, and professional accountability. Strengthening community engagement can further support compliance, creating bottom-up accountability that complements administrative obligations and sustains quality midwifery practice. Conclusion: Effective completion of the MCH Handbook by midwives depends on a combination of intrinsic motivation, external regulations, supportive systems, and community engagement, which together ensure accurate documentation, quality care, and professional accountability.